Creative training in creating advertising content on social media for entrepreneur students - Isalman, Isalman; Mubaraq, Ahmad; Conny, Conny; Purwati Ningtyas, Ajeng (Society : Jurnal Pengabdian Masyarakat, 2025)
Creative training in creating advertising content on social media aims to improve students' skills in designing effective, aesthetic advertisements, and being able to increase brand awareness and sales. This program is intended for entrepreneurial students of the Faculty of Economics and Business, Halu Oleo University who have businesses or interests in digital marketing. This one-day training takes place in a computer laboratory, covering three stages: preparation, implementation, and evaluation. The preparation stage includes participant identification, module preparation, and provision of tools such as laptops and design applications. During the implementation, participants receive theoretical material on digital marketing, visual design, storytelling, and copywriting, followed by direct practice using design applications such as Canva to create content in the form of images or short videos. The results of the work are then presented to get input. This training improves participants' ability to design relevant and attractive advertisements, as well as understand the importance of social media algorithms and data-based strategies to maximize reach. In addition to encouraging consumer engagement, the training equips participants with practical skills that can support the success of their businesses in the digital era. With the right creative content, students are expected to be able to increase sales while creating business sustainability